Evidentiary Application Of Arbitration In The Indonesian Legal System - Asmaul Husna; Alfania Pane; Bima Ilman Mirazha Hasibuan (ISNU Nine-Star Multidisciplinary Journal, 2024)
In the dispute resolution mechanism both litigation and non-litigation such as arbitrary, proofing evidence process plays essential role to reconstruct the real occurrence in order to seek the truth. Proofing principles that is used in Indonesian arbitrary process is based on the Law number 30 year 1999 on arbitrary and alternative dispute resolution that is lex arbitri for Indonesia. Arbitrary is part of formal civil law, therefore its proofing principles is basically the same with the dispute resolution trough litigation. The Law number 30 year 1999 shows that Even though Indonesia is a civil law jurisdiction, there are some common law principles that are accommodated in the arbitrary process. Using conceptual and statute approach, this article attempts to look at proofing principles may arise in arbitrary mechanism based on the law mentioned and based on the actual practice.